A lógica de Lewis Carroll - Lindemann, John Lennon (2018)
The present dissertation presents an examination of the Carrollian logic through the reconstruction of its syllogistic theory. Lewis Carroll was one of the main responsible for the dissemination of logic during the nineteenth century, but most of his logical writings remained unknown until a posthumous publication of 1977. The reconstruction of the Carrollian syllogistic theory was based on the comparison of the two books on author's logic, "The Game of Logic" and "Symbolic Logic". The analysis of the Carrollian syllogistics starts from a study of the historical context of development of the logic and the developments of syllogistics previous to the contribution of the author. Situated in the historical period of algebraical logic, Carrollian syllogistics is characterized as a conservative extension of the Aristotelian syllogistics, the main innovation is the use of negative terms and the introduction of a diagrammatic method suitable for the representation of negative terms. The diagrammatic method of the Carrollian syllogistics presents advances in relation to the methods of Euler and Venn. The use of negative terms also requires a redefinition of the notion of syllogism, simplifying and expanding the amount of arguments amenable to logical treatment. Carroll does not use four, but only three categorical propositions in his syllogistic, with interpretation of existential presuppositions congruent with a syntactic-existential reading. Carrollian syllogistics uses some techniques found in the work of algebraists of logic and also made the same confusions between notions of "class" and "member" that were common in the period. Convinced of the social utility of logic and dedicated to popularize it, Carroll priorized a creation of new didactics for the teaching of logic in his works, where he can include his diagrammatic method of solving syllogisms. Carroll made only scant considerations of his conception of logic. Based on the small considerations found throughout the study and on the constant claim of the social utility of logic, it is suggested that Carroll is close to the so-called pragmatic position, which considers a logic as an instrument of regulation of discourse.